Reconceptualization of Rehabilitation for Recidivists in the Persective of Dignified Justice - I Made Wirya Darma (University of Udayana, 2023)
A relapse condition is when the former addicts and victims of narcotics abusers who have undergone treatment at a rehabilitation center may return to taking narcotics. This relapse patient in legal terms is called a recidivist. Law Number 35 of 2009 concerning Narcotics regulates sanctions for actions in the form of rehabilitation for addicts and victims of narcotics abusers, but does not regulate whether or not a recidivist can receive rehabilitation sanctions. In this study, there are three issues that will be discussed, namely rehabilitation measures in overcoming drug abuse, rehabilitation sanctions for recidivist addicts and victims of narcotics abusers and reconceptualization of rehabilitation in the perspective of dignified justice. This research is a normative juridical research that examines the void of norms regarding the imposition of rehabilitation crimes for recidivists. The research analysis was carried out qualitatively. The rehabilitation action is motivated by the view that addicts and victims of narcotics abusers are victims. By itself, drug abuse is a victimless crime. The Law on Narcotics does not regulate rehabilitation sanctions for recidivist addicts and victims of narcotics abusers, so that in law enforcement practice there are several people who have been sentenced to rehabilitation sanctions before and in subsequent cases are still subject to rehabilitation sanctions. Reconceptualization of rehabilitation in the perspective of dignified justice places recidivists as victims; therefore, as long as the person is only an addict and a victim of narcotics abuse, he is still entitled to receive rehabilitation sanctions.